STRATEGI PENGEMBANGAN MATA PENCAHARIAN ALTERNATIF UNTUK MENINGKATKAN PENDAPATAN RUMAH TANGGA NELAYAN DI PULAU KODINGARENG KOTA MAKASSAR - Nursanti Jumardi; Syahrul Djafar; Andi Tamsil (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2018)
This study aims to: (1) To indentify socio-economic characteristicsof fishing communities in Kodingareng island; (2) Formulate alternative livelihoodsto increase the income of fisherman households in kodingareng village; (3)Develop alternative livelihoodsto increase the income of fisherman households in kodingareng village of Makassar. The research was conducted on 01 September to 31 October 2018 on the Kodingareng Island of Makassar City. The method used in this study is: descriptive analysis, business feasibility analysis, and SWOT analysis. The results of the study indicate that alternative livelihoods that are feasible to develop are fiberglass manufacturing business, abon fish processing business, and fish cracker processing business. Suggestions and strategies that need to be considered include : (1) Conduct socialization, counseling and technical training in the hope that that the community, especially fisherman when not fishing, will continue to increase economic income but not conduct destructive activities; (2) Reactivate processing groups with guidance and supervision starting from raw material preparation, production, distribution, and marketing processes; (3) Need to get support and facilitation from the government, related to alterntive livelihoods that will be developed such as technical assistance and building business partnership patterns to obtain capital provision and broader market access.